Dacarbazine (DTIC) versus vaccination with autologous peptide-pulsed dendritic cells (DC) in first-line treatment of patients with metastatic melanoma: a randomized phase III trial of the DC study group of the DeCOG - Schadendorf, Dirk; Ugurel, Selma; Rittgen, Werner; Edler, Lutz; Sucker, Antje (Annals of oncology, 2020)
Background: This randomized phase III trial was designed to demonstrate the superiority of autologous peptide-loaded dendritic cell (DC) vaccination over standard dacarbazine (DTIC) chemotherapy in stage IV melanoma patients. Patients and methods: DTIC 850 mg/m2 intravenously was applied in 4-week intervals. DC vaccines loaded with MHC class I and II-restricted peptides were applied subcutaneously at 2-week intervals for the first five vaccinations and every 4 weeks thereafter. The primary study end point was objective response (OR); secondary end points were toxicity, overall (OS) and progression-free survival (PFS). Results: At the time of the first interim analysis 55 patients had been enrolled into the DTIC and 53 into the DC-arm (ITT). OR was low (DTIC: 5.5%, DC: 3.8%), but not significantly different in the two arms. The Data Safety & Monitoring Board recommended closure of the study. Unscheduled subset analyses revealed that patients with normal serum LDH and/or stage M1a/b survived longer in both arms than those with elevated serum LDH and/or stage M1c. Only in the DC-arm did those patients with (i) an initial unimpaired general health status (Karnofsky = 100) or (ii) an HLA-A2+/HLA-B44− haplotype survive significantly longer than patients with a Karnofsky index <100 (P = 0.007 versus P = 0.057 in the DTIC-arm) or other HLA haplotypes (P = 0.04 versus P = 0.57 in DTIC-treated patients). Conclusions: DC vaccination could not be demonstrated to be more effective than DTIC chemotherapy in stage IV melanoma patients. The observed association of overall performance status and HLA haplotype with overall survival for patients treated by DC vaccination should be tested in future trials employing DC vaccines.
Elektronische Reproduktion der Druckausgabe
Gesehen am 22.12.2020